2010
DOI: 10.1167/iovs.10-5429
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Damage as a Potential Mechanism for Age-Related Macular Degeneration

Abstract: Collectively, the data indicate that mtDNA is preferentially damaged with AMD progression. These results suggest a potential link between mt dysfunction due to increased mtDNA lesions and AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
213
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(215 citation statements)
references
References 44 publications
2
213
0
Order By: Relevance
“…11 Increased mitochondrial damage and generation of reactive oxygen species (ROS) are associated with AMD, suggesting that damaged mitochondria and other oxidatively modified components are not efficiently removed by the aged-RPE cell. 11,12 Autophagy is especially crucial in the maintenance of homeostasis of the RPE since these cells are exposed to sustained oxidative stress. 6 A number of studies have reported that autophagy occurs in the RPE.…”
Section: Introductionmentioning
confidence: 99%
“…11 Increased mitochondrial damage and generation of reactive oxygen species (ROS) are associated with AMD, suggesting that damaged mitochondria and other oxidatively modified components are not efficiently removed by the aged-RPE cell. 11,12 Autophagy is especially crucial in the maintenance of homeostasis of the RPE since these cells are exposed to sustained oxidative stress. 6 A number of studies have reported that autophagy occurs in the RPE.…”
Section: Introductionmentioning
confidence: 99%
“…The daily phagocytosis of photoreceptor outer segments by the RPE leads to the accumulation of the phototoxin N-retinyl-N-retinylidene ethanolamine (A2E) and other compounds that can inhibit mitochondrial function (13,14,17), possibly through oxidative damage (18). mtDNA isolated from macular RPE of individuals with AMD exhibits significantly more damage than that from age-matched controls (19). Genetic studies implicate several mtDNA haplotypes (20,21) and a nuclear gene encoding a mitochondria-associated protein (22) as AMD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of genetic linkage and next-generation sequencing (NGS) technologies has led to significant insights into the role of mitochondrial mutations in driving disease processes [3,4]. Mitochondrial disorders can be subdivided into three classes: (i) primary mitochondrial disorders caused by mutations in mitochondrial genes; (ii) disorders with mutations in nuclear genes involved in mitochondrial function; and (iii) secondary disorders that arise from the accumulation of mitochondrial damage over time frequently involving neurodegenerative pathologies [5][6][7][8]. Tissues such as retina, brain, and muscle, which have enormous energy requirements, are particularly vulnerable to variations in mitochondrial function.…”
Section: Mitochondrial Dysfunction In Human Disordersmentioning
confidence: 99%
“…Approximately 50% of mitochondrial disorders have an ocular phenotype [9]. In addition to dominant optic atrophy (DOA) [10] and LHON (Box 1 [11]), mitochondrial dysfunction has been linked to multifactorial diseases, including age-related macular degeneration (AMD) [7,12] and diabetic retinopathies [12], as well as complex disorders involving multiple tissues, including the eye, such as neuropathy, ataxia and retinitis pigmentosa (NARP) and Kearns-Sayre syndrome (KSS) [13,14].…”
Section: Mitochondrial Dysfunction In Human Disordersmentioning
confidence: 99%